Strategi Guru dalam Mengatasi Kedisiplinan Belajar Siswa pada Mata Pelajaran PAI di Kelas IV SD Negeri 106 Kota Bengkulu - Hengki Sastrisno; Andre Taulany Sandi; Windamayanti Pohan; Olin Yuanra (MODELING: Jurnal Program Studi PGMI, 2026)
This study was motivated by persistent issues regarding student learning discipline in Islamic Religious Education classes—such as non-compliance with rules, a lack of responsibility in completing assignments, and insufficient student engagement in the learning process. These conditions highlight the importance of teacher strategies in fostering and enhancing student learning discipline starting at the elementary school level. This study aims to describe the strategies employed by the teacher to address student learning discipline in Islamic Religious Education classes for Grade IV students at SD Negeri 106 Bengkulu City. A qualitative method with a descriptive approach was utilized. The research subjects—comprising the Islamic Religious Education teacher, Grade IV students, and parents—were selected using purposive sampling. Data collection involved observation, interviews, and documentation, while data analysis proceeded through stages of data reduction, data presentation, and conclusion drawing; data validity was verified through source and technique triangulation. The results indicate that the teacher’s strategies for addressing student learning discipline involved setting an example, habituation, rule enforcement, providing motivation and counsel, and implementing educational rewards and punishments. The application of these strategies successfully improved student compliance with rules, responsibility in completing assignments, and student awareness regarding orderly participation in the learning process. Thus, consistently applied teacher strategies play a crucial role in shaping student learning discipline in Islamic Religious Education, thereby supporting a more effective and conducive learning environment.